2005
DOI: 10.1007/s10803-005-0041-6
|View full text |Cite
|
Sign up to set email alerts
|

ERPs and Eye Movements Reflect Atypical Visual Perception in Pervasive Developmental Disorder

Abstract: Many studies of eye tracking or event-related brain potentials (ERPs) in subjects with Pervasive Developmental Disorder (PDD) have yielded inconsistent results on attentional processing. However, recent studies have indicated that there are specific abnormalities in early processing that are probably related to perception. ERP amplitudes in response to visual stimuli, measured above the occipital (modality-specific) cortex, are reported to be abnormally small in patients with PDD, and the abnormal visual proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…For example, attention in individuals with ASD may be more easily captured by differences in the salience of stimuli. There is certainly some evidence that these individuals are more sensitive to discrepancies in visual stimulation (Kemner & van Engeland, 2006). Alternatively, the comparator hypothesis (Reed et al, 2008) would predict that discrepancy in salience would trigger differences in the degree of associative strength accruing to each of the stimuli, which may be enough to trigger a performance difference in individuals with ASD, but not in individuals with a less sensitive comparator mechanism.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, attention in individuals with ASD may be more easily captured by differences in the salience of stimuli. There is certainly some evidence that these individuals are more sensitive to discrepancies in visual stimulation (Kemner & van Engeland, 2006). Alternatively, the comparator hypothesis (Reed et al, 2008) would predict that discrepancy in salience would trigger differences in the degree of associative strength accruing to each of the stimuli, which may be enough to trigger a performance difference in individuals with ASD, but not in individuals with a less sensitive comparator mechanism.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas, a study employing event-related potential (ERP) to investigate eye movement (Kemner & van Engeland, 2006) suggested that individuals with ASD display abnormalities in early visual processing related to the processing of faces, and to the specificity of spatial frequency processing.…”
Section: Introductionmentioning
confidence: 99%
“…Some possible reasons for these findings can be suggested. The tasks we used to measure hippocampus and dorsolateral prefrontal cortex functioning also required more fundamental processes involved in visual-spatial processing; these processes may be affected in autism (Bertone et al, 2005;Kemner & Van Engeland, 2006), which could lead to deficits in both the Spatial Memory Span and Spatial Delayed Alternation tasks. Impairment in these tasks across the full range of developmental levels in the Autism group may indicate that difficulty in more basic processes, such as the representation of visual-spatial information, affected spatial memory abilities in general.…”
Section: General Conclusionmentioning
confidence: 99%
“…In the perceptual domain, the majority of scientific studies have reported atypical processing in aspects of visual perception and visual attention ranging from characteristically nonsocial stimuli and tasks, such as discrimination of chromatic stimuli (e.g., Franklin et al, 2010), cast shadow (Becchio, Mari, & Castiello, 2010), static gratings (e.g., Bertone, Mottron, Jelenic, & Faubert, 2005), moving dots (e.g., Milne et al, 2002, Pellicano et al, 2005), and complex objects (e.g., “Greebles”) (e.g., Behrmann et al, 2006, Davies et al, 1994), to social stimuli, including faces (e.g., Dalton et al, 2005, Kemner and van Engeland, 2006), eye gaze (e.g., Elsabbagh et al, 2009), and biological motion (e.g., Blake et al, 2003, Klin et al, 2009; for a review, see Simmons et al, 2009). Theories of autistic perception have explained these findings in terms of a “detail-focused” perceptual style (Frith & Happé, 1994), generally enhanced perceptual functioning (Mottron et al, 2006), or reduced generalization (Plaisted, 2001).…”
Section: Introductionmentioning
confidence: 99%